Analysis of magnetic field harmonics change due to manufacturing error in air-core HTS quadruple magnet. (March 2019) - Kim, Junseong; Baek, Geonwoo; Lee, Jeyull; Choi, Yojong; Han, Seunghak; Song, Seunghyun; Ko, Tae Kuk
Highlights: Manufacturing errors are inevitable occurred during making a magnet. HTS tape has a larger error in thickness and width than that of LTS. Change of field quality of the quadruple magnet by manufacturing error. Field properties of the quadrupole magnet are affected by manufacturing error. Symmetry of the quadruple magnet is distorted by manufacturing error. Abstract: An high temperature superconducting (HTS) quadruple magnet used to focus and defocus beams in particle accelerator has been studied for overcoming the disadvantages of low temperature superconducting (LTS) quadruple magnet. LTS quadruple magnet is hard to withstand radiation and heat load at hot cell because of small thermal margin of LTS, and has a nonlinear magnetic characteristic due to iron-core. The thermal margin is improved by changing the LTS to HTS. The magnetic field components are linear according to the operation current by removing the iron-core. Therefore, the air-core HTS quadruple magnet was designed in the past research. Field qualities that determine the performance of the quadruple magnet are composed of field gradient, field uniformity and effective length, and those of air-core HTS quadruple magnet can be achieved using harmonic matching (HM) method. However, when the quadruple magnet is fabricated, parameters of the fabricated magnet are different from designed parameters due to the manufacturing errors. This manufacturing error, REBCO conductor's dimensional variation of thickness and width, and human errors during winding and assembling, could crucially influence to the field qualities of the quadruple magnet. In this paper, we present a draft design of air-core HTS quadruple magnet and describes an analytical method to predict change of field gradient, uniformity and effective length caused by manufacturing errors and (3) an evaluation of the permissible manufacturing error for an air-core HTS quadruple magnet.